Classification of historic buildings in Indonesia with svd algorithm based on texture and color characteristics (case: temples, historic mosques, historic churches, and historic Confucian temples). Issue 1 (December 2020) - Hadiyanto,; Dolok Lauro, Manatap; Herwindiati, Dyah Erny
Abstract: This study aims to make an application that able to make classification for historical building in Indonesia. The building types being used in this study are: temples, historic mosques, historic churches and historic confucian temples. This application classifies historical buildings based on texture, Color and combination of two. GLCM method is utilzied for texture characteristics classification. Histogram method is being used for Color characteristics. SVD method is used to reduce dimensions, which can make classification process becomes faster.